Dietary diversity and depression: cross-sectional and longitudinal analyses in Spanish adult population with metabolic syndrome. Findings from PREDIMED-Plus trial - Naomi Cano-Ibáñez; Lluis Serra-Majem; Sandra Martín-Peláez; Miguel Ángel Martínez-González; Jordi Salas-Salvadó; Dolores Corella; Camille Lassale; Jose Alfredo Martínez; Ángel M Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; et al. (Public Health Nutrition, 2023)
Abstract